FEASIBILITY ANALYSIS OF RED CHILI FARMING IN SIDODADI RAMUNIA, BERINGIN SUB-DISTRICT - Rahmat Suryanto Pirngadi; Dewi Novina Sukapiring; Khairuna Utami; Nelfita Rizka S Depari (Jurnal Ilmiah Teunuleh, 2022)
Farming is a science that studies how a person coordinates and cultivates production factors in the form of land and the natural surroundings as capital so that they can provide the best possible benefits. Farming feasibility analysis is a study to observe and analyze the feasibility of a business, which observes several parameters about whether or not a business is feasible. The business can be said to be feasible if the profits obtained can cover all the costs used in the form of direct and indirect costs. This study aims to analyze the feasibility level of red chili farming in Sidodadi Ramunia Village, Beringin Sub-District, Deli Serdang District, North Sumatera. The method used in this research is the method of sampling, interviews and questionnaires, data from parties or related agencies that have the authority to collect data related to the object of research. The results showed that based on the value of the Benefit Cost Ratio (B/C Ratio) this business was not feasible because it did not provide benefits to the red chili farmers in Sidodadi Ramunia Village, while based on the value of the Revenue Cost Ratio (R/CRatio) red chili farming was feasible. to be cultivated because the revenue received is greater than the total costs incurred by the red chili farmers in Sidodadi Ramunia Village.